2006
DOI: 10.1007/s10535-005-0089-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought stress on photosynthetic gas exchange, chlorophyll fluorescence and stem diameter of soybean plants

Abstract: Changes in plant growth, photosynthetic gas exchange, chlorophyll fluorescence and stem diameter of soybean [Glycine max (L.) Merr.] plants under drought stress were studied. Total plant dry mass was reduced by 30 % compared to wellwatered control plants. Leaf water potential was slightly decreased by water stress. Water stress induced daytime shrinkage and reduced night-time expansion of stem. Photosynthetic rate, stomatal conductance and transpiration rate were significantly declined by water stress, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
116
1
19

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 20 publications
9
116
1
19
Order By: Relevance
“…Reduction of shoot mass is a strategy to control the loss of water under drought (Ohashi et al, 2006). In addition, plants may also avoid dehydration by changing the allocation pattern of C between shoots and roots to allow for exploitation of deeper soil layers with longer root systems (Lopes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of shoot mass is a strategy to control the loss of water under drought (Ohashi et al, 2006). In addition, plants may also avoid dehydration by changing the allocation pattern of C between shoots and roots to allow for exploitation of deeper soil layers with longer root systems (Lopes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the increase in the value of F 0 /F m in Si-treated plants under water-deficit conditions (Figure 9). Several studies have reported stress-induced increases in the values of F 0 /F m and q N and decreases in F v /F m , q P , F 0 , and φPSII (Yordanov et al, 2000;Baker and Rosenqvist, 2004;Ohashi et al, 2006;Habibi and Hajiboland, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Unfavorable growing conditions such as excessive soil water and agricultural practices such as late planting, reduction in the ratio of red to far-red light (R : FR) and high plant density, reduce seed yield primarily by reducing branch growth and branch seed yield per plant (Green-Tracewicz et al, 2010). Water stress at the seedling and at the flowering stage decreases soybean yield by 20 and 46%, respectively (Shou et al, 1991) due to decreased photosynthetic rate, stomatal conductance and transpiration rate of soybean (Ohashi et al, 2006;Vu et al, 2001). Moreover, shade treatments have been shown to reduce yield and seed size (Tang et al, 2010) and also to reduce yield with no effect on seed size (Andrade and Ferreiro, 1996).…”
Section: Introductionmentioning
confidence: 99%